Impacts of Soil Temperature on Apricot Productivity in Malatya, Turkey: A Longitudinal Analysis Using Inverse Distance Weighting - Altıngöller, Melike; Karakurt, Melisa; Şengün, M. Taner; Karadeniz, Enes; Sunbul, Fatih (Uğur ÇAKILCIOĞLU, 2024)
This longitudinal study analyzes the impact of soil temperature on apricot productivity in Malatya, Turkey, from 2004 to 2022. Utilizing Inverse Distance Weighting (IDW) to correlate detailed soil temperature maps with apricot yield and production data, we identify significant temperature-dependent variations in apricot yields. Our findings reveal that optimal soil temperature management is crucial for maximizing apricot productivity, as deviations from ideal soil temperatures correlate strongly with yield fluctuations. Specifically, periods of increased soil temperatures generally correspond with higher productivity, highlighting the delicate balance required for optimal apricot cultivation. This research underscores the importance of integrating climate considerations into agricultural planning and offers valuable insights for developing adaptive strategies to enhance apricot production in the face of global climate variability. By mapping the spatial and temporal dynamics of soil temperature and its impact on apricot yield, this study contributes to the broader discourse on sustainable agricultural practices and the economic resilience of the apricot sector in Malatya.
Keywords: Conservation and Biodiversity; Koruma ve Biyolojik Çeşitlilik